Development of brake system model for educational purpose - Amirulnizam, Mohd (2008)
The process of braking system is actually simple but yet, the public still do not understand how it works. There are many available braking systems for educational purpose in the market but it is quite expensive. So, a low cost braking system model is needed for the learning process. The objective of the project is to build the car brakes structure and assembly system for educational, analysis the structure of the brakes and determine the design properties of the brakes. Fabrication work is to design a stand for car brake system model. The structure analysis is carried out using Algor software and the design properties are determined using theoretical calculation. From the structure analysis, it is shows that the structure is safe and did not exceed the yield strength when the parts are connected to the stand. In design properties analysis, it is calculated that the maximum force that should give to the pedal is 377.46 N as the maximum static coefficient of friction is 0.7. If the tire is locked and car is slide, the kinetic coefficient is used instead of static coefficient.